Patient Characteristics Influence Activated Signal Transducer and Activator of Transcription 3 (STAT3) Levels in Primary Breast Cancer—Impact on Prognosis - Nilsson, Linn; Sandén, Emma; Khazaei, Somayeh; Tryggvadottir, Helga; Nodin, Björn; Jirström, Karin; Borgquist, Signe; Isaksson, Karolin; Jernström, Helena (Frontiers in Oncology, 2020)
Background: Activated signal transducer and activator of transcription 3 (pSTAT3) is often present in breast cancer, but its prognostic impact is still unclear. We investigated how breast tumor-specific pSTAT3Y705 levels are associated with patient and tumor characteristics and risk of recurrence. Materials and Methods: Primary breast cancer patients without preoperative treatment were included preoperatively. The patients were treated in Lund, Sweden, in 2002–2012 and followed until 2016. Levels of pSTAT3Y705 were evaluated in 867 tumors using tissue microarrays with immunohistochemistry and categorized according to the H-score as negative (0–9; 24.2%), intermediate (10–150; 69.9%), and high (160–300; 5.9%). Results: Patients were followed for up to 13 years, and 137 recurrences (88 distant) were recorded. Higher pSTAT3Y705 levels were associated with patient characteristics including younger age, any alcohol consumption, higher age at first child birth, and smaller body size, as well as tumor characteristics including smaller tumor size, lower histological grade, lymph node negativity, progesterone receptor positivity, and HER2 negativity (all Ptrends ≤ 0.04). Higher pSTAT3Y705 levels were associated with lower risk of early recurrences (LogRank Ptrend = 0.10; 5-year LogRank Ptrend = 0.004) and distant metastases (LogRank Ptrend = 0.045; 5-year LogRank Ptrend = 0.0007), but this was not significant in the multivariable models. There was significant effect modification between tamoxifen treatment and pSTAT3Y705 negativity on the recurrence risk in chemonaïve patients with estrogen receptor positive tumors [adjusted hazard ratio (HR) 0.38; Pinteraction = 0.046]. Conclusion: Higher pSTAT3Y705 levels were associated with several patient and tumor characteristics that are mainly associated with good prognosis and a tendency toward lower risk for early recurrences. In the future, these results may help guide the selection of patients for trials with drugs targeting the STAT3 pathway.